2019
DOI: 10.1111/cea.13496
|View full text |Cite
|
Sign up to set email alerts
|

Ara h 7 isoforms share many linear epitopes: Are 3D epitopes crucial to elucidate divergent abilities?

Abstract: Background The peanut allergens Ara h 2, h 6, and h 7 are potent allergens and can trigger severe reactions. Ara h 7 consists of three isoforms differing in their ability to induce basophil degranulation, whereas the ability of Ara h 7.0201 is comparable to Ara h 2 and 6 as shown in previous literature. Objective To identify linear epitopes of Ara h 7.0101, Ara h 7.0201 and Ara h 7.0301 recognized by IgE and IgG4 from patients sensitized to Ara h 7 and to investigate their potential to elucidate divergent abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…51,52 The evidence of clinical utility of such tests has been recently systematically reviewed. 53,54 The most recent studies have focused on peanut [55][56][57][58] and cow's milk 59,60 allergies as well as allergies to shellfish [61][62][63] and legumes. [64][65][66] Using a peptide microarray, Caubet et al 60 identified a greater intensity and broader diversity of IgE binding in children with persistent CMA, which decreased as children became tolerant.…”
Section: Specific Ige To Allergen Epitopesmentioning
confidence: 99%
“…51,52 The evidence of clinical utility of such tests has been recently systematically reviewed. 53,54 The most recent studies have focused on peanut [55][56][57][58] and cow's milk 59,60 allergies as well as allergies to shellfish [61][62][63] and legumes. [64][65][66] Using a peptide microarray, Caubet et al 60 identified a greater intensity and broader diversity of IgE binding in children with persistent CMA, which decreased as children became tolerant.…”
Section: Specific Ige To Allergen Epitopesmentioning
confidence: 99%
“…The microarray incubation was performed as previously described 14 . Briefly, patient sera were diluted 1:4 in WSUB and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Ehlers and colleagues found that they have similar linear epitopes and so they must therefore differ in terms of their conformational epitopes. 73…”
Section: The Increasing Number Of Peanut and Tree Nut Allergen Compmentioning
confidence: 99%
“…Three have been identified with differing potential to degranulate basophils in an ex vivo system. Ehlers and colleagues found that they have similar linear epitopes and so they must therefore differ in terms of their conformational epitopes 73 …”
Section: Allergensmentioning
confidence: 99%